Megaoesophagus secondary to oesophagitis and oesophageal stricture associated with doxycycline therapy in a domestic shorthair kitten - Namira, N. E.; Lim, M. Y.; Watanabe, Malaika; Khor, Kuan Hua (Veterinary Association Malaysia, 2015)
Oesophageal strictures associated with doxycycline therapy in cats are a rare occurrence but several cases have been reported. A 3-month-old kitten was presented to University Veterinary Hospital, Universiti Putra Malaysia (UVH-UPM) with the primary complaint of persistent vomiting. The kitten was prescribed with doxycycline two weeks prior to presentation. Regurgitation was observed during hospitalisation. Radiographs and endoscopy performed revealed findings consistent with a megaesophagus cranial to an oesophageal stricture located at the region of the second thoracic vertebrae.